Anesthetic and Obstetrical Factors Associated With the Effectiveness of Epidural Analgesia for Labor Pain Relief: An Observational Population-Based Study. Issue 4 (August 2017) - Bonnet, M. P.; Prunet, C.; Baillard, C.; Kpéa, L.; Blondel, B.; Le Ray, C.
Abstract : (Abstracted from Reg Anesth Pain Med, 42(1):109–116, 2017) Epidural analgesia is considered the criterion standard for pain relief during labor because of its high rate of maternal satisfaction and minimal adverse effects for both mother and child. However, pain relief during labor is also a complex issue, and there continue to be efforts to improve epidural analgesia.